Histoplasmosis with Deep CNS Involvement: Case Presentation with Discussion and Literature Review - Hariri, Omid R.; Minasian, Tanya; Quadri, Syed A.; Dyurgerova, Anya; Farr, Saman; Miulli, Dan E.; Siddiqi, Javed (Journal of Neurological Surgery Reports, 2015)
Central nervous system (CNS) histoplasmosis is rare and difficult to diagnose because it is often overlooked or mistaken for other pathologies due to its nonspecific symptoms. A 32-year-old Hispanic man with advanced acquired immunodeficiency virus presented with altered mental status and reported confusion for the past 3 months. He had a Glasgow Coma Scale of 12, repetitive nonfluent speech, and a disconjugate gaze with a right gaze preference. Lung computed tomography (CT) findings indicated a pulmonary histoplasmosis infection. Magnetic resonance imaging of the brain revealed a ring-enhancing lesion in the left caudate nucleus. A CT-guided left retroperitoneal node biopsy was performed and indicated a benign inflammatory process with organisms compatible with fungal yeast. Treatment with amphotericin B followed by itraconazole was initiated in spite of negative cerebrospinal fluid (CSF) cultures and proved effective in mitigating associated CNS lesions and resolving neurologic deficits. The patient was discharged 3 weeks later in stable condition. Six weeks later, his left basal ganglia mass decreased. Early recognition of symptoms and proper steps is key in improving outcomes of CNS histoplasmosis. Aggressive medical management is possible in the treatment of intracranial deep mass lesions, and disseminated histoplasmosis with CNS involvement can be appropriately diagnosed and treated, despite negative CSF and serology studies.
Keywords: Histoplasma capsulatum; disseminated histoplasmosis; CNS infection; fungal yeast; CSF culture; ring-enhancing lesion; immunocompromised; human immunodeficiency virus